2012
DOI: 10.1007/s10812-012-9579-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and vibrational IR spectra of a UCl4⋅2DMSO complex

Abstract: UDC 539.19 Structural models are designed and spectral characteristics are computed based on DFT calculations for a complex of uranium tetrachloride with two molecules of dimethylsulfoxide (UCl 4 ⋅2DMSO). The calculations were carried out using a B3LYP hybrid functional in the LANL2DZ effective core potential approximation for the uranium atom and a cc-pVDZ all-electron basis set for all other atoms. Two structural variants were found for the complex. In the first of them, which is more stable, DMSO molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The first can be easily assigned to the asymmetric stretching of the system, where two bonds U–Cl are elongated, while the other two become shorter. This is in line with a number of experimental and theoretical studies, where this is reported in a window comprised between 320 and 350 cm 1 101–103 . When we transition to the periodic system (green) this peak undergoes a strong redshift, where it is shifted to 96 cm 1 due to the strongly hindered stretching of the bonds induced by the crystalline structure, as each chlorine is shared between two Uranium atoms.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The first can be easily assigned to the asymmetric stretching of the system, where two bonds U–Cl are elongated, while the other two become shorter. This is in line with a number of experimental and theoretical studies, where this is reported in a window comprised between 320 and 350 cm 1 101–103 . When we transition to the periodic system (green) this peak undergoes a strong redshift, where it is shifted to 96 cm 1 due to the strongly hindered stretching of the bonds induced by the crystalline structure, as each chlorine is shared between two Uranium atoms.…”
Section: Resultssupporting
confidence: 91%
“…This is in line with a number of experimental and theoretical studies, where this is reported in a window comprised between 320 and 350 cm À1 . [101][102][103] When we transition to the periodic system (green) this peak undergoes a strong redshift, where it is shifted to 96 cm À1 due to the strongly hindered stretching of the bonds induced by the crystalline structure, as each chlorine is shared between two Uranium atoms. The opposite trend can be observed for the peak at 78 cm À1 (blue) which corresponds to the bending of the molecule and it undergoes a strong blueshift when we move to the solid state structure at 255 cm À1 .…”
Section: Uranium Chloride Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis seems to prove that DMSO solvent is a better surfactant than DMF solvent which is similar to interpretations done by previous researchers [49][50][51][52]. Thus, DMSO has an unique property to coordinate with the central atom in certain instances not only through the O atom but also via the S atom [53].…”
Section: Ftir Analysissupporting
confidence: 88%
“…The hybrid exchange-correlation functional B3LYP was also used in all calculations [25][26][27]. The approximation used in the calculations was also successful for modeling the structure and vibrational spectra of U-containing compounds (UO 2 Cl 2 , UCl 4 , and their complexes) [28,29]. LMOs were constructed by the Edmiston and Ruedenberg method [30].…”
mentioning
confidence: 99%